Perbandingan Kebangkrutan Menggunakan Model Altman Z Score, Model Springate dan Model Zmijweski - Agustina, Ariefa Nur (Jurnal Ilmiah Poli Bisnis, 2022)
This study aims to examine more deeply the comparison of the bankruptcy of the Altman Z-Score, Springate, and Zmijewski models in companies listed on the Indonesia Stock Exchange in the pharmaceutical and food and beverages sector for the period 2015-2020. This research is a quantitative research using secondary data with a research population of 42 companies and a research sample of 12 companies with a sampling technique using purposive sampling. The data collection method is done by accessing the annual financial reports published by the Indonesia Stock Exchange. The data obtained were then processed using the IBM SPSS Statistic 25 tool. This analysis included descriptive statistical tests, classical assumption tests (normality tests), and hypothesis tests (paired samples test, accuracy test). The results showed that the Altman Z-Score model was significantly different from the Springate model, the Altman Z-Score model was significantly different from the Zmijewski model, the Springate model was significantly different from the Zmijewski model. The accuracy test shows that the Zmijewski model has the highest level of accuracy in predicting bankruptcy.